Healthcare Systems Management: Methodologies and Applications 21st Century Perspectives of Asia (Managing the Asian Century,, 2018)
This edited volume focuses on research conducted in the area of healthcare systems management. Chapters are extensions of works presented at the International Conference on Management of Ergonomic Design, Industrial Safety and Healthcare Systems. The book addresses the need to have the knowledge of technological and resource management, clinical performances and quality of healthcare delivery systems in order to make hospital systems well and adequately designed and operationally effective ensuring the quality of healthcare to patients. It is a useful resource for students, researchers, industrial professionals and design engineers.